Performance psychology : perception, action, cognition, and emotion - Raab, Markus; Lobinger, Babett; Hoffmann, Sven; Pizzera, Alexandra; Laborde, Sylvain (Amsterdam : Academic Press, 2015)
This book integrates findings from across domains in performance psychology to focus on core research on what influences peak and non-peak performance. The book explores basic and applied research identifying cognition-action interactions, perception-cognition interactions, emotion-cognition interactions, and perception-action interactions. The book explores performance in sports, music, and the arts both for individuals and teams/groups, looking at the influence of cognition, perception, personality, motivation and drive, attention, stress, coaching, and age. This comprehensive work includes contributions from the US, UK, Canada, Germany, and Australia.
Overview5 -- Bridging the Gap between Action and Cognition: An Overview; COGNITION AND ACTION; THE YIPS IN GOLF; Neurological Origin: Focal Dystonia; Psychological Origin: Choking; Motor Origin: Dynamic Stereotype; Diagnosing and Treating the Yips; THE EDUCATION OF SOCCER COACHES; TALENT IDENTIFICATION AND ASSESSMENT IN HIGH-PERFORMANCE SPORTS; CONCLUSION; REFERENCES; 6 -- Improving Performance by Means of Action-Cognition Coupling in Athletes and Coaches; THE PROFESSION OF COACHING; PURPOSE; DEVELOPMENT OF COACHING EXPERTISE; History of Leadership in Sport; Behavioral Theories.
CIP data; item not viewed.
Keywords: Attitude (Psychology); Performance; Attitude (Psychology); Performance; Electronic books